ENGLISH-INDONESIAN CODE MIXING FOUND IN THE SUMMER TRIANGLE NOVEL BY HARA HOPE - Larassati, Difa; Suyudi, Ichwan (Universitas Gunadarma, 2021)
Code mixing is a phenomenon that occurs everywhere. In Indonesia, it is found that the people often mix their language with other languages, one of which is English. The mixing of these two languages is found not only in spoken but also in written form. The aims of this research are to find out the types of code mixing, the reasons for code mixing, and the syntactic units of code mixing in the Summer Triangle novel by Hara Hope. The data studied are narrations and utterances of the characters which contain English-Indonesian code mixing. The researcher uses the qualitative method and documentation technique in this research. In examining the data, the researcher uses theories from Hoffman (1991), Savile-Troike (1986), and other experts. The result of the research shows that there are 216 data of code mixing in the Summer Triangle novel. The types of code mixing found are intra-sentential code mixing (87.04%), intra-lexical code mixing (6.02%), and involving a change of pronunciation (6.94%). The reasons for code mixing found are talking about a particular topic (48.61%), quoting somebody else (2.32%), being emphatic about something (7.87%), interjection (inserting sentence fillers or sentence connectors) (3.24%), repetition used for clarification (2.32%), intention of clarifying the speech content for interlocutor (6.94%), expressing group identity (2.78%), softening or strengthening request or command (1.85%), real lexical need (11.11%), and prestige (12.96%). The English syntactic units found are word (61.11%), phrase (31.94%), clause (2.78%), and abbreviation (4.17%).